Leadership for social justice and democracy in our schools - Blankstein, Alan M.; Houston, Paul D.; HOPE Foundation (Bloomington, Ind.); American Association of School Administrators (Thousand Oaks : Corwin Press, 2011)
"This ninth and final book in The Soul of Educational Leadership series offers practical strategies for promoting socially responsible school cultures that enhance student engagement"-- Provided by publisher.
"The ninth and final book in The Soul of Educational Leadership series, this volume offers school and district leaders ideas and strategies for leading in ways that promote social justice and democracy in our schools. With contributions from key figures such as Bonnie Davis, Linda Skrla, and Randall Lindsey among others, this book explores transformative leadership, self-reflection, modeling, ways of rethinking equity and prosocial school cultures as well as models for becoming an equity-oriented change agent and leading schools of character in order to foster greater student engagement and achievement"-- Provided by publisher.
Machine generated contents note: PrefaceAbout the EditorsAbout the Contributors1. Respect - Bonnie M. Davis2. Social Justice: Focusing on Assets to Overcome Barriers - Randall B. Lindsey, Delores B. Lindsey, and Raymond D. Terrell3. Becoming an Equity-Oriented Change Agent - Linda Skrla, Kathryn Bell McKenzie, and James Joseph Scheurich4. Are Women Prepared to Be School Superintendents? An Essay on the Myths and Misunderstandings - C. Cryss Brunner and Yong-Lyun Kim5. Leading Schools of Character - Marvin W. Berkowitz6. Teaching Social Responsibility - Sheldon H. Berman7. Zero Indifference and Teachable Moments: School Leadership for Diversity, Inclusion and Justice - Mara Sapon-Shevin8. Getting Kids Ready for School - Raising the Village - Paul D. HoustonIndex
"A joint publication with the Hope Foundation and the American Association of School Administrators."
Includes bibliographical references and index.
Keywords: School management and organization; Educational leadership; Social justice; Democracy and education; EDUCATION / Leadership